Analisis Faktor Explicit Knowledge dan Tacit Knowledge Untuk Penerapan Human Capital Management System - Handrie Noprisson (JSAI (Journal Scientific and Applied Informatics), 2025)
In the era of a knowledge-based economy, Human Capital Management System (HCMS) has become increasingly important, particularly in the context of higher education. This study aims to analyze the influence of tacit knowledge sharing and explicit knowledge sharing on the human capital of university students. A quantitative approach was used by collecting data from 430 students through an online survey, with 420 valid responses analyzed using the Structural Equation Modeling (SEM) method. The results indicate that tacit knowledge sharing has a more significant impact on Human Capital than explicit knowledge sharing, with a t-statistics value of 6.777 and a P-Value of 0.000, demonstrating a strong and significant relationship. Meanwhile, the relationship between explicit knowledge sharing and human capital showed a t-statistics value of 1.777 with a p-value of 0.076, which remains within the hypothesis acceptance threshold but is less dominant. The implications of this study suggest that universities should design HCMS strategies that focus more on strengthening tacit knowledge sharing, such as mentoring, group discussions, and experiential learning programs. Additionally, technology-based learning management systems remain essential for documenting and distributing explicit knowledge.